2010
DOI: 10.1002/mrc.2620
|View full text |Cite
|
Sign up to set email alerts
|

NMR chemical shifts as a tool to analyze first principles molecular dynamics simulations in condensed phases: the case of liquid water

Abstract: We present (1)H NMR chemical shift calculations of liquid water based on first principles molecular dynamics simulations under periodic boundary conditions. We focus on the impact of computational parameters on the structural and spectroscopic data, which is an important question for understanding how sensitive the computed (1)H NMR resonances are upon variation of the simulation setup. In particular, we discuss the influence of the exchange-correlation functional and the size of the basis set, the choice for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…The approach developed by Sebastiani and Parrinello, 66 which was shown to give good estimation of NMR shifts, 67 was used. Similar to the procedures adopted by Banyai et al, 68 30 structures were extracted from a NPT MD trajectory of a system of 32 water molecules and the nuclear magnetic shieldings were calculated with the BLYP method 69,70 and the Goedecker type pseudopotentials 71 for the two hydrogen atoms in all water molecules, using the NMR module implemented in the CPMD program. 72 This results in 2 × 32 × 30 = 1920 data points for which the average was evaluated to represent the final nuclear magnetic shielding of the water hydrogens for the SWM6 model.…”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach developed by Sebastiani and Parrinello, 66 which was shown to give good estimation of NMR shifts, 67 was used. Similar to the procedures adopted by Banyai et al, 68 30 structures were extracted from a NPT MD trajectory of a system of 32 water molecules and the nuclear magnetic shieldings were calculated with the BLYP method 69,70 and the Goedecker type pseudopotentials 71 for the two hydrogen atoms in all water molecules, using the NMR module implemented in the CPMD program. 72 This results in 2 × 32 × 30 = 1920 data points for which the average was evaluated to represent the final nuclear magnetic shielding of the water hydrogens for the SWM6 model.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The good performance of SWM6 in reproducing the experimental g OO (r) suggests that the local water structure in bulk phase is better reproduced with the new model. To further characterize properties related to the local water structure, NMR shielding, and the related chemical shifts, which are sensitive indictors of the local hydrogen bonding structure, were calculated following the protocol used by Banyai et al 68 It was shown that the applied density functional method based protocol can give chemical shifts that are close to the experimental value for the bulk water structures collected from ab initio MD simulations. 68 The results are shown in Table IV 99 However, with the same simulation setups as used by Banyai et al, 68 it can be concluded that the SWM6 model yields local hydrogen bonding structures that are closer to the ab initio MD structures when compared to the other tested models.…”
Section: E Bulk Phasementioning
confidence: 99%
“…Therefore, various physical effects such as van der Waals interactions between molecules and the quantum behaviour of nuclei have to been reproduced only approximately or even completely neglected. In addition, the high computational cost of AIMD imposes severe restrictions on the size of a model system and time length of the simulations thus introducing additional finite-size errors and statistical uncertainties into the properties calculated [99][100][101][102][103][104][105][106][107] .…”
Section: Liquid Water a Structural And Dynamical Properties Of Lmentioning
confidence: 99%
“…The self-consistent field (SCF) convergence was set to 6 10 À7 a.u. [32][33][34] We used the deuteron mass for the hydrogen atoms and a time step of 1 fs. The system was thermostatically controlled to 350 K by using a CSVR thermostat [31] with a time constant of 100 fs.…”
Section: Computational Detailsmentioning
confidence: 99%